2018
DOI: 10.1038/s41598-018-23404-4
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism for activating IgA production by Pediococcus acidilactici K15 and the clinical impact in a randomized trial

Abstract: IgA secretion at mucosal sites is important for host defence against pathogens as well as maintaining the symbiosis with microorganisms present in the small intestine that affect IgA production. In the present study, we tested the ability of 5 strains of lactic acid bacteria stimulating IgA production, being Pediococcus acidilactici K15 selected as the most effective on inducing this protective immunoglobulin. We found that this response was mainly induced via IL-10, as efficiently as IL-6, secreted by K15-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 54 publications
2
48
0
1
Order By: Relevance
“…Probiotics promote IgA maturation in formula-fed infants by increasing the serum levels of soluble CD14 ( Rautava et al., 2006 ). P. acidilactici supplementation has been shown to promote IL-6 and IL-10 production by dendritic cells to increase mucosal IgA content in humans ( Kawashima et al., 2018 ). We observed that probiotic supplementation increased the caecal IL-10 content in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics promote IgA maturation in formula-fed infants by increasing the serum levels of soluble CD14 ( Rautava et al., 2006 ). P. acidilactici supplementation has been shown to promote IL-6 and IL-10 production by dendritic cells to increase mucosal IgA content in humans ( Kawashima et al., 2018 ). We observed that probiotic supplementation increased the caecal IL-10 content in this study.…”
Section: Discussionmentioning
confidence: 99%
“…293 Pediococcus acidilactici K15, one of the strains of lactic acid bacteria whose bacterial RNA endows DCs to secrete IL-6 and IL-10, resulting in increased B cell-derived sIgA at mucosal sites in humans. 294 Intriguingly, crosstalk between gut microbiome and IgA is not limited in the gut. For example, intestinal commensal also exerts evident effects on the serum IgA repertoire.…”
Section: Microbiota-mediated Modulation Of Th1 Cellsmentioning
confidence: 99%
“…DC-SIGN and MR are involved in IgA recognition by DCs [125]. Recognition of IgA by DCs is accompanied by inhibition of the Th1 cytokine IL-12 [126] and increased IL-10 production [127]. Increased IgA production in the intestine may have a regulatory effect on intestinal DCs.…”
Section: β-Glucansmentioning
confidence: 99%